2000
DOI: 10.1016/s0082-0784(00)80208-8
|View full text |Cite
|
Sign up to set email alerts
|

Flamelet modeling of lifted turbulent methane/air and propane/air jet diffusion flames

Abstract: The stabilization mechanism of lifted turbulent jet diffusion flames is a test problem for models of partially premixed turbulent combustion. In these flames, combustion processes occur in both the nonpremixed and the premixed mode. For the flame stabilization process, however, flame propagation of the premixed branches seems to play a crucial role. In this paper, a flamelet model for partially premixed turbulent combustion is presented that combines flamelet models for non-premixed and premixed combustion. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Few numerical studies address the problem of ignition of turbulent diffusion flames in complex configurations. Such simulations require treatment of both premixed and non-premixed combustion modes [27][28][29][30]. Richardson [31] and Richardson and Mastorakos [32] have discussed ignition of turbulent diffusion flames using a Reynolds Averaged Navier-Stokes (RANS) -Conditional Moment Closure (CMC) modeling: results suggest that the first order CMC reaction rate closure seems inadequate for such configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Few numerical studies address the problem of ignition of turbulent diffusion flames in complex configurations. Such simulations require treatment of both premixed and non-premixed combustion modes [27][28][29][30]. Richardson [31] and Richardson and Mastorakos [32] have discussed ignition of turbulent diffusion flames using a Reynolds Averaged Navier-Stokes (RANS) -Conditional Moment Closure (CMC) modeling: results suggest that the first order CMC reaction rate closure seems inadequate for such configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The burning velocity prior to the expansion of the burned gas is estimated by combining an analysis conducted by Chen et al [8], which gives the turbulent burning velocity as a function of the turbulence strength for the flame, with an estimate of the turbulence strength at the flame front. The Chen et al correlation is an asymptotic combination of a turbulent diffusion model, originally proposed by Damköhler [9], and a limiting value for the turbulent flame speed obtained from experiments.…”
Section: Changes To Turbulent Velocity Multipliermentioning
confidence: 99%
“…Thus, a formulation for both premixed and nonpremixed combustion has to be used. In order to properly account for the turbulence-chemistry interaction in the partially premixed turbulent lifted jet flames, the present study has adopted the level-set-based flamelet approach suggested by Chen et al [12]. In this approach, the flamelet model of non-premixed combustion is combined with the level-set approach for premixed combustion.…”
Section: Level-set-based Flamelet Approachmentioning
confidence: 99%
“…The mixing of fuel and oxidizer in the turbulent flow field is described by transport equation of mean mixture fraction and its variance [5]. For the convenience of presentation, the important part of the level-set-based flamelet formulations proposed by Chen et al [12] is described here.…”
Section: Level-set-based Flamelet Approachmentioning
confidence: 99%
See 1 more Smart Citation